CURSO PREPARATÓRIO DE MATEMÁTICA PARA ENGENHARIA: A EXPERIÊNCIA DA UNIJUÍ - OLIVEIRA, DIANGO; CAMPOS, MAURÍCIO D.; SALVADORI, FABIANO; POZZOBON, CRISTINA; RECH, CASSIANO; REIMBOLD, MANUEL M. P.; BOLACELL, JÚLIO C. O. (Salão do Conhecimento, 2013)
Resumo